2009
DOI: 10.4018/jossp.2009010102
|View full text |Cite
|
Sign up to set email alerts
|

Tools for the Study of the Usual Data Sources found in Libre Software Projects

Abstract: Due to the open nature of Free/Libre/Open Source software projects, researchers have gained access to a rich set of development-related information. Although this information is publicly available on the Internet, obtaining and analyzing it in a convenient way is not an easy task and many considerations have to be taken into account. In this paper we present the most important data sources that can be found in libre software projects and that are studied by the research community: source code, source code mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Robles et al [44] describe the problems that can be found when retrieving and preparing for OSS data analysis and present the tools that support data retrieval for OSS evolution analysis: source code, source code management systems, mailing lists, and bug tracking systems. In accordance with this study, Bachmann and Bernstein [5] address the quality of data sources and provides insights into the influencing factors to the quality and characteristics of software process data gathered from bug tracking database and version control system log files.…”
Section: Evolution Process Supportmentioning
confidence: 99%
“…Robles et al [44] describe the problems that can be found when retrieving and preparing for OSS data analysis and present the tools that support data retrieval for OSS evolution analysis: source code, source code management systems, mailing lists, and bug tracking systems. In accordance with this study, Bachmann and Bernstein [5] address the quality of data sources and provides insights into the influencing factors to the quality and characteristics of software process data gathered from bug tracking database and version control system log files.…”
Section: Evolution Process Supportmentioning
confidence: 99%
“…Retrieval of mailing list information. We used MLStats [7] to retrieve mail messages from the development mailing list 1 , and store them in a MySQL database.…”
Section: Initial Observationsmentioning
confidence: 99%
“…Retrieval of Git information. We used CVSAnalY [7] to retrieve information from the main Xen git repository 2 , and store it in a MySQL database as well.…”
Section: Initial Observationsmentioning
confidence: 99%
“…To study the communication across several releases, we retrieved data for 32 months spanning from January 2009 to August 2011. We used MLStats [64] to split into threads the mailing list archive data sets. We chose this period because it comprises 5 release cycles, including the transition between two major releases-from the series 2.x to 3.x.…”
Section: Data Collection and Cleaningmentioning
confidence: 99%